Influência dos modelos de turbulência na análise térmica computacional de equipamentos eletrônicos - Martins, Alessandro Morais [UNESP] (2015)
For all equipment and electronic components function, properly efficient heat exchange is required between the elements and the means to prevent overheating. At first, it was used natural convection as the primary form of heat dissipation. However, with the miniaturization of electronic components and the increasing power of these components was necessary to increase the air flow for heat dissipation and thus passed to using forced convection to maintain the equipment within the temperature ranges recommended. Then, with the gradual increase in flow velocities were thus generated flows increasingly turbulent, which are a great ally when seeking a larger heat exchange. Thus, the purpose of this paper is to present a study of the phenomena occurring on an electronic board subjected to turbulent flow through numerical simulations and perform a comparison with existing experimental result in the literature. To analyze the influence of each turbulence model applied to the case study. Therefore, it was observed that there is a great difficulty for anyone working with numerical simulation to define which model to use among the various models of turbulence and is in this respect that this work is based, to facilitate the choice of turbulence model and point out which turbulence model best describes the problem proposed here. To this end, heated blocks on an electronic board were subjected to flows with speeds ranging from 1m/s to 4m/s, being the most used in industry for this type of flow and through study and refinement of the meshes, the analysis of flows, speeds and temperature distributions sought to verify the turbulence model that best describes the problem here chosen